OFAT Adoption on FAl2O3-POE Nanolubricant Absorbance Ratio Optimization Based on Spectrophotometric Method - Nugroho, Agus; Rizalman, Mamat; Bo, Zhang; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Yusaf, Talal (Springer, Singapore, 2023)
The UV visible spectrophotometry technique is one of the methods for determining a nanolubricant's stability standard. The absorbance level of a nanolubricant is determined by spectrophotometry. This method measures how well the nanolubricant absorbs UV rays from a light source. In this study, one factor at a time (OFAT) based on surface response was adopted to determine the effect of wavelength selection on the absorbance ratio of FAl2O3-POE nanolubricant. The FAl2O3-POE sample was prepared using a two-steps ap-proach. The sample was ultrasonicated for 100 min using a homogenizer. UV visible spectrophotometry analysis was performed on day 1 and 15 to determine the absorbance ratio. Sixteen runs were performed using a quadratic design to acquire experimental data were fitted. The ANOVA analysis discovered that the experimental statistics were well suited to the polynomial model, with an R2 value of 0.9951 and a model F-value of 1316.47. The findings suggest that the optimum wavelength is 375 nm with an absorbance value of 0.935473 and a de-sirability level of 1.0.